Uma Proposta de Aplicação da Programação Linear no Ensino Médio - Rosa, José Vinicius Barreto dos Santos (2021)
In this work, we analyze the contents about System of Linear Equations and Inequations offered in High School, aiming to work with Linear Programming. We present some concepts and theoretical results to verify the LPP solution in a vertex of the viable region. We bring a proposal to present the LPP from the modification in the statement of a problem about the equation systems proposed to High School. As part of a class plan, we analyze the methods of graphical resolution and exhaustion of a Linear Programming Problem in the R 2 space, and present a tutorial of “a free tool available in OpenOffice Calc, named Solver”, for cases where there is no graphic solution.